2003
DOI: 10.1002/ffj.1199
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Nepeta crassifolia Boiss. & Buhse oil from Iran

Abstract: Hydrodistillation of volatile oil from the aerial parts at full flowering stage of Nepeta crassifolia Boiss. & Buhse was analysed by a combination of GC and GC-MS. Twenty-one components were characterized in the oil layer. The main constituents were 4aα,7α,7aα-nepetalactone (92.6%), linalyl acetate (2.6%), piperitone (0.80%), germacrene D (0.73%), 4aβ ,7α,7aβ-nepetalactone (0.64%) and β-caryophyllene (0.58%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…The components of the oils were identified by their retention indices relative to C 9 -C 28 n-alkanes, and by comparison of their mass spectra with those of authentic samples or with data already available in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Identification Of Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The components of the oils were identified by their retention indices relative to C 9 -C 28 n-alkanes, and by comparison of their mass spectra with those of authentic samples or with data already available in the literature [5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Identification Of Componentsmentioning
confidence: 99%
“…The chemical constituents of the essential oils of N. cataria and N. crassifolia growing in Mazandaran province of Iran were studied in view of its different climatic conditions as compared to area studied earlier [5][6][7][8][9][10][11] . Isolation of essential oils: The dried flowering aerial parts of N. cataria and N. crassifolia were subjected to hydrodistillation using a Clevenger-type apparatus for 5 h to yield 0.94% and 0.82% of yellowish oils, respectively.…”
mentioning
confidence: 99%
“…(7), N. pogonosperma Jamzad et Assadi (8), N. crassifolia Boiss. et Buhse (9)(10), N. meyeri Benth. (11), N. fissa C.A.…”
Section: Introductionmentioning
confidence: 99%
“…Among the constituents of the volatile oil, 4aα,7α,7aα-nepetalactone (87.1%), 4aα,7α,7aβ-nepetalactone (3.1%), β-caryophyllene (2.5%), and β-pinene (1.7%) were the major ones; the other constituents were present in relatively small amounts, representing only (3.6%) of the total oil. Nepetalactone isomers, which are the major constituens in our oil, were present in the essential oil of several Nepeta spp [11][12][13][14][15][16][17][18][19][20]. It was found that nepetalactones were responsible for the feline attractant properties of Nepeta species.…”
mentioning
confidence: 94%